Bimatoprost, latanoprost, and tafluprost induce differential expression of matrix metalloproteinases and tissue inhibitor of metalloproteinases. Issue 1 (December 2016) - Yamada, Hiroshi; Yoneda, Masahiko; Gosho, Masahiko; Kato, Tomohiro; Zako, Masahiro
Abstract Background Differences in the increase in matrix metalloproteinase (MMP) and decrease in tissue inhibitor of metalloproteinase (TIMP) activity may contribute to the different characteristics observed clinically on decreased intraocular pressure in patients with glaucoma or ocular hypertension. The purpose of this study was to investigate differences in the expression profiles of MMPs and TIMPs induced by the prostaglandin analogs bimatoprost, latanoprost, and tafluprost in human non-pigmented ciliary epithelial cells (HNPCECs). Methods HNPCECs were cultured for 24 h with 0, 10, 100, or 1000 μM of the free acid forms of bimatoprost, latanoprost, and tafluprost. We measured the expression levels of MMPs and TIMPs using real-time polymerase chain reaction, and compared the results. Enzyme activities of MMP-2 and −9 in conditioned media were measured by gelatin zymography. Results All prostaglandin analogs we examined dose-dependently increased expression levels of MMP-1, −2, −3, −9, and −17, whereas expression levels of TIMP-1 and −2 decreased with increasing concentrations of each analog. Each prostaglandin analog induced different levels of increases in MMPs and decreases in TIMPs. Conclusions Unique expression profiles of MMPs and TIMPs induced by bimatoprost, latanoprost, and tafluprost, as shown in HNPCECs, may contribute to clinically different effects on intraocular pressure decreases in patients with glaucoma or ocular hypertension.